2011
DOI: 10.1098/rspa.2011.0508
|View full text |Cite
|
Sign up to set email alerts
|

Graph theory and the Jahn–Teller theorem

Abstract: The Jahn-Teller (JT) theorem predicts spontaneous symmetry breaking and lifting of degeneracy in degenerate electronic states of (nonlinear) molecular and solid-state systems. In these cases, degeneracy is lifted by geometric distortion. Molecular problems are often modelled using spectral theory for weighted graphs, and the present paper turns this process around and reformulates the JT theorem for general vertex-and edgeweighted graphs themselves. If the eigenvectors and eigenvalues of a general graph are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…To interpret these results theoretically, simple tight-binding models 2 , 30 , 31 were constructed and analyzed as follows (Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…To interpret these results theoretically, simple tight-binding models 2 , 30 , 31 were constructed and analyzed as follows (Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the course of performing calculations on individual molecules by means of this HLPM approach a problem has, from time-to-time, been encountered whenever, on application of the Aufbau Principle, [11,[20][21][22][23][24] the π-electronic ground-state configuration of the conjugated hydrocarbon in question is found to be a triplet ground-state. We have occasionally noted specific examples of this phenomenon as we have serendipitously come across them in our previously reported work.…”
Section: Introductionmentioning
confidence: 99%
“…approach [9,10] is frequently cast, these are the eigenvalues and eigenvectors, [11,21] respectively, of the vertex-adjacency matrix [8] of that associated labelled molecular-graph. [8] (b) Then the Aufbau process [20][21][22][23][24] is applied, during the course of which the available π-electrons are distributed amongst these calculated energy-levels in order to determine a π-electron ground-state configuration for the hydrocarbon in question. If the Aufbau procedure has been successful -which is not always the case, as is discussed in Refs.…”
mentioning
confidence: 99%
“…Along these lines, Clone(K n ) was considered in [7], where it was shown that with few exceptions, Clone(K n ) is the only m-sheeted covering graph of K n , for m ≤ n − 1, such that the full automorphism group of K n has a lift. On the other hand, Clone(K 5 ) was studied in connection with a graph-theoretical interpretation of the Jahn-Teller effect [2]. In order to clarify the role of degenerate eigenvalues (that is, eigenvalues having higher multiplicities) in the Jahn-Teller distortion, graphs with symmetry group S 5 were sought [3].…”
Section: Discussionmentioning
confidence: 99%